2013
DOI: 10.17795/semj16652
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Intestinal Parasitic Infection in School Going Children in Amalapuram, Andhra Pradesh, India

Abstract: Background:The public health impact of parasitic infection has been consistently underestimated in the past, but there is now a general consensus that diseases caused by intestinal parasites represent an important public health problem, especially children. Recent studies suggest that even moderate intensity of infection may have adverse effects on growth, iron deficiency anemia and cognitive function, practically for children of school age. Objective: Aim of the present study was to determine the intestinal p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 4 publications
1
13
0
Order By: Relevance
“…Also this study is in agreement with Ullah et al, (2014) (36) , who reported that the percentage of parasitic infection among school children was (73.87%). Another study conducted by Ashok et al, (2013) (37) , showed high prevalence of parasitic infection 63.9%. However, our result was higher than several studies done in Egypt which include a study done in Damietta Governorate by Mohammad et al, (2012) (38) , a study done in Al-Azhar and Assiut university hospitals by Bauomy et al, (2010) (34) and a study done in Tanta, Gharbia Governorate by Ahmed (2013) (39) , which they reported that about one third and about one quarter (30.7%, 38.5% and 22.43%) of school pupils respectively had intestinal parasitic infections.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Also this study is in agreement with Ullah et al, (2014) (36) , who reported that the percentage of parasitic infection among school children was (73.87%). Another study conducted by Ashok et al, (2013) (37) , showed high prevalence of parasitic infection 63.9%. However, our result was higher than several studies done in Egypt which include a study done in Damietta Governorate by Mohammad et al, (2012) (38) , a study done in Al-Azhar and Assiut university hospitals by Bauomy et al, (2010) (34) and a study done in Tanta, Gharbia Governorate by Ahmed (2013) (39) , which they reported that about one third and about one quarter (30.7%, 38.5% and 22.43%) of school pupils respectively had intestinal parasitic infections.…”
Section: Discussionmentioning
confidence: 89%
“…Infection with intestinal parasites has known to cause iron deficiency anemia, growth retardation in children and other physical and mental health problems. Furthermore, chronic intestinal parasitic infections have become the subject of speculation and investigation in relation to the spreading and severity of other infectious diseases of viral origin, tuberculosis and malaria (19)(20)(21) . Although treatment with the current anti-helminthic can significantly reduce parasite burdens, chemotherapy alone is unlikely to prevent reoccurring infections with GI nematodes.…”
Section: Introductionmentioning
confidence: 99%
“…[4,17,18,19,20,21] This study showed ten cases (9.80%) of mixed parasitic infection, which was in concordance with study at Bihar. [7] Few studies showed high prevalence of mixed parasitic infection, [28] while others showed low prevalence. [4,20] …”
Section: Discussionmentioning
confidence: 99%
“…However the findings of our study were in accordance with the findings of Tsuyuoka et al, in Brazil and Okyay et al, in Turkey, where the prevalence among school children was found to be 42% and 31.8%, respectively. 4,5 In India, a wide variation in the prevalence of parasitic infection is noted in different studies from different regions was found to be as low as 11.4% in a study conducted by Kotian [6][7][8][9] These wide differences are due to heterogeneity of study populations, socio demographic characters and various study locations.…”
Section: Discussionmentioning
confidence: 99%